PENGGUNAAN APLIKASI SISTEM INFORMASI GEOGRAFIS DALAM PEMETAAN PERSEBARAN PEMBERI PELAYANAN KESEHATAN TINGKAT PERTAMA DALAM RANGKA PERSIAPAN PENYELENGGARAAN SISTEM JAMINAN SOSIAL NASIONAL DI KOTA DENPASAR - Juliantini, Luh Putu Eka; Mulyawan, Ketut Hari (ARCHIVE OF COMMUNITY HEALTH; Vol 2 No 1 (2013): Juni (2013))
To achieve health coverage for all citizen of Indonesia, the government has launched a socialinsurance namely “Sistem Jaminan Sosial Nasional (SJSN)” which will be implemented in 2014.In the social insurance“Pemberi Pelayanan Kesehatan tingkat I, PPK I, have a central role as gatekeeper. This study purposed to gain information about the distribution of PPK I in the capital cityof Bali Province and assessed need level PPK I of Bali. The distribution and need level of PPK Ican be seen using Geographic Information System (GIS).This research was a cross-sectional descriptive study. Population and sample in this researchware all PPK I which registered in PT. Askes (Persero) and all of population in Denpasar.GIS analysis showed that PPK were not evenly distributed. PPK I distributed mostly in the centreof Denpasar. Based on cluster map can be seen that the highest clustered PPK I located in centreand West Denpasar area.PPK I need level map showed the mosted needed area was Pemogan village. PPK I need levelmap can be used by PT. Askes (Persero) to determine the PPK I need level in Denpasar city. It willbe easier for PT. Askes (Persero) to determine priority of distribution of PPK I.
Keywords: GIS, Distribution of PPKI, PPK I need level